Cidades do interior do Amazonas - Possibilidade de autonomia econômica com aproveitamento dos recursos naturais renováveis - Almeida, Roger Luiz Paz de (2010)
This work shows how the proposed development of the inner cities of Amazonas State through a participatory planning, democratic and inclusive, in the form of a model for preparation of Master Plans, considering the Amazon reality in the midst of their socio economic. Additionally, this work presents an approach to municipal planning through urban instruments, considering the political and economic partner as well as the problem of environmental context, resulting in inefficient operation of the municipal laws in force. In this sense the Master Plan is presented as essential and basic, to guide policy development and urban expansion, allowing municipalities to organize themselves, establishing an orderly urban growth, considering also its surroundings. On the search for elements that make possible the intent of this research, launches out of hand a discussion of the pursuit of full employment, considered as a principle regulator of economic activity, from incentives to private initiative, encouraging the creation and maintenance levels employment, given that full employment is presented as a relentless quest to achieve improvements in quality of life. Thus the model proposed by this thesis attempts to trace a way to rethink new forms of production organization and territorial urban and rural, to redefine the relationship between producers and nature, from the rational use of natural resources, establishing a relationship directly proportional to population needs in the state of Amazonas. Key Words:Urban Máster Plan.Amazon State Counties And Sustainable Development